SUBSTITUTION OF SHRIMP FLOUR AND TEMPEH IN MAKING TORTILLA CHIPS AS A HIGH-PROTEIN SNACK - Wanda Meilani; Ratih Kurniasari; Fathma Syahbanu (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
One of the snacks that are widely favored by children is tortilla chips, but generally contain high carbohydrates but low protein. Shrimp flour and tempeh can be substituted in making tortilla chips to increase protein content. Shrimp flour contains 48.83% protein, while tempeh flour contains 27.73% protein. This study aims to substitute shrimp flour and tempeh in making tortilla chips as a high-protein snack. This study used a true experimental design with a Completely Randomized Design (CRD) with 3 treatment levels, namely F1 (10:20), F2 (15:15), and F3 (20:10). The results showed that the best formulation was F2 (15:15) with the characteristics of brownish yellow color, slightly fragrant shrimp, slightly salty taste, crunchy texture, and slightly bitter aftertaste. The best formulation contains 3.42% water, 0.09% acid-insoluble ash, 16.28% protein, 19.44% fat, 53.04% carbohydrates, and 452.24 kcal/100 g total energy. The protein content of the best formulation has met the requirements for a high protein claim. The conclusion of this study is that the substitution of rebon shrimp flour and tempeh in tortilla chips can be used as a high-protein snack. This product has the potential to be used as a functional snack to prevent stunting in children.